ANALISIS PENGARUH MUTASI DAN PROMOSI JABATAN PADA PENINGKATAN KARIR PEGAWAI - Abdullah Zailani (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study examines the Effect of Mutation and Promotion ofPosition on Employee Career Development. The research was conductedby using survey method conducted on automotive company. The result ofthe research shows that Mutation and Promotion of Position onEmployee Career Development have positive and significant influence.The existence of mutations and promotion in a company if managedproperly so that generate a positive impact, then employees will be moreresponsible for the work they live.